Strategi Portal Waspada Online (Wol) dalam Menerapkan Berita Kriminal - Silviana Silviana; Taufik Wal Hidayat; Armansyah Matondang (Jurnal Ilmu Pemerintahan, Administrasi Publik, dan Ilmu Komunikasi (JIPIKOM), 2023)
The study delves into the Strategy of Online Alert Portal (WOL) in Managing Criminal News. Its objective is to understand the strategies employed by the Waspada Online portal in handling criminal news and to identify the obstacles in processing such news. This qualitative research utilizes both primary and secondary data sources with data collection methods that involve observation, interviews, and documentation. The study involves three key informants: the Managing Editor, Criminal Journalist, and Coverage Coordinator. The study is underpinned by the Agenda Setting Theory. The research findings reveal that Waspada Online uses strategies involving press releases from the police and utilizes the 5W+1H elements in the development of criminal news content. Various challenges faced by journalists include difficulty in obtaining and interviewing informants, remote and inaccessible locations, and network instability. Solutions to address these obstacles include communication with family for information and disguising themselves as the general public to obtain necessary news.